Quality of life and wellbeing in patients receiving electroconvulsive therapy: a study from Kashmir - Mushtaq, Raheel; Shoib, Sheikh; Dar, Mohammad Maqbool; Shah, Tabindah; Mushtaq, Sahil; Singh, Rameshwar Manhas (International Journal of Research in Medical Sciences, 2017)
Background: Electroconvulsive therapy (ECT) is an effective neurostimulative treatment in psychiatric disorders and is widely used throughout the world except few countries. Studies regarding quality of life and well-being in patients receiving electroconvulsive therapy have not been undertaken in our country. Objective of current study was to study the quality of life and well-being in patients receiving Electroconvulsive therapy. Methods: 50 patients who have been prescribed pharmacological drugs form the control group and 50 patients already on psychotropic medication who were prescribed electroconvulsive therapy form the case group were taken up for study. Detailed evaluations were carried out clinically and by measurement of Well-being index. Pre-treatment evaluation was carried out one day before Electroconvulsive therapy, and post treatment was carried out at 3 and 7 week. Data were evaluated by means of chi square and Repeat ANOVA, Post hoc Bonferroni correction for within group comparisons applicable. Results: Mean wellbeing index for study group is 14 which is slightly higher than control (11) (p>0.001.) Well-being index of study group is much higher than that of control group at 3 and 7 week post treatment (p>0.001). Conclusions: Sustained effect on quality of life remains in depression up to 7 weeks and in mania it responds rapidly wanes off within 7 weeks. Electroconvulsive therapy improves the quality of life in psychiatric patients.